Performance optimization of microbial electrolysis cell (MEC) for palm oil mill effluent (POME) wastewater treatment and sustainable Bio-H2 production using response surface methodology (RSM). (22nd April 2022) - Kadier, Abudukeremu; Wang, Junying; Chandrasekhar, K.; Abdeshahian, Peyman; Islam, M. Amirul; Ghanbari, Farshid; Bajpai, Mukul; Katoch, Surjit Singh; Bhagawati, Prashant Basavaraj; Li, Hui; Kalil, Mohd Sahaid; Hamid, Aidil Abdul; et al.
Abstract: Microbial electrolysis cells (MECs) are a new bio-electrochemical method for converting organic matter to hydrogen gas (H2 ). Palm oil mill effluent (POME) is hazardous wastewater that is mostly formed during the crude oil extraction process in the palm oil industry. In the present study, POME was used in the MEC system for hydrogen generation as a feasible treatment technology. To enhance biohydrogen generation from POME in the MEC, an empirical model was generated using response surface methodology (RSM). A central composite design (CCD) was utilized to perform twenty experimental runs of MEC given three important variables, namely incubation temperature, initial pH, and influent dilution rate. Experimental results from CCD showed that an average value of 1.16 m 3 H2 /m 3 d for maximum hydrogen production rate (HPR) was produced. A second-order polynomial model was adjusted to the experimental results from CCD. The regression model showed that the quadratic term of all variables tested had a highly significant effect (P < 0.01) on maximum HPR as a defined response. The analysis of the empirical model revealed that the optimal conditions for maximum HPR were incubation temperature, initial pH, and influent dilution rate of 30.23 ∘ C, 6.63, and 50.71%, respectively. Generated regression model predicted a maximum HPR of 1.1659 m 3 H2 /m 3 d could be generated under optimum conditions. Confirmation experimentation was conducted in the optimal conditions determined. Experimental results of the validation test showed that a maximum HPR of 1.1747 m 3 H2 /m 3 d was produced. Graphical abstract: Image 1 Highlights: POME used in MEC for H2 as a feasible method and effective treatment technology. To enhance H2 production from POME, an empirical model was generated using RSM. Results from CCD showed 1.16 m 3 H2 /m 3 d for maximum HPR was produced. The confirmation test results showed a maximum HPR of 1.1747 m 3 H2 /m 3 d.